Smart Village Tourism: Barriers and Facilitators in Adopting a Smart City Perspective Using SWOT Analysis - Widarti, Erni; Erkamim, Moh.; Nugraha, Tegar Wijanarko Surya (Diponegoro University, 2025)
This disruptive era, tourist villages must adapt to technological advancements to innovate and drive the digitalization of these villages. Data processing, speed, and clarity of information can be utilized for the development of smart village tourism, where innovation and technology become the main drivers of transformation. The smart city concept can be adopted in the development of smart village tourism to enhance sustainability in tourist villages. A deep and ongoing study of the potential and local wisdom of rural communities is a key factor in the development of smart village tourism. This research serves as a preliminary study in the context of smart village tourism. The aim of this study is to formulate a development model for smart village tourism based on the identification and analysis of the barriers and facilitators in adopting the smart city perspective. The case studies involve two tourist villages in Boyolali Regency. The data analysis method uses SWOT analysis (Strengths, Weaknesses, Opportunities, Threats). SWOT analysis is useful for evaluating various aspects of tourist villages and identifying strategies that can be implemented for development and improvement. These findings represent an initial step towards formulating the development of smart village tourism by adopting a smart city perspective based on an ICT model, aligned with local potential and wisdom as key factors for the sustainability of tourist villages.